Upaya Meningkatkan Hasil Belajar Matematika Materi Pecahan Senilai Melalui Model Realistic Mathematics Education Siswa Kelas IV SDN 44 Bengkulu Tengah - Sunyiati, Sunyiati (Jurnal PGSD, 2021)
This research aims to improve the activities and results of learning mathematics using the  Realistic Mathematics Education model for grade IV students of SDN 44 Bengkulu Tengah. This type of research is a classroom action research conducted in two cycles. The subjects of this study was grade IV students of SDN 44 Bengkulu Tengah. The data collection instrument used the teacher activity observation sheet, student activity and learning results tests. The data analysis technique uses arithmetic mean and the percentage of learning completeness. The results showed: 1) teacher activity in the first cycle obtained an average of 3.20 increased to the second cycle obtained an average of 3.70, 2) student activity in the first cycle obtained an average of 3.30 and in the second cycle obtained an average -average 3.60, 3) Learning result in the first cycle obtained an average of 68.75 with learning completeness 62.5%, increased in the second cycle an average value of 80 with learning completeness 87.5%. The conclusion of this study that the use of the Realistic Mathematics Education model can improve the activity and learning result of fourth grade students of SDN 44 Bengkulu Tengah